1997
DOI: 10.1016/s0885-3924(96)00275-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving cancer pain management in communities: Main results from a randomized controlled trial

Abstract: The purpose of this randomized controlled community trial is to evaluate the effects of a community intervention utilizing opinion leaders and educational strategies on the cancer pain management knowledge, attitudes, and the practices of physicians and nurses, and cancer pain reported by patients. Six Minnesota communities participated in the study. The three communities randomized to the intervention received educational programs over 15 months. The clinical community opinion leaders participated in a minife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
8

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 41 publications
0
82
0
8
Order By: Relevance
“…25 This study queried respondents to rate themselves on a 1 to 5 scale (with 1 being low and 5 being high) for 6 items, including talking to colleagues, amount of information given during conversations, frequency of requests for information, relative likelihood of sharing with or receiving ideas from colleagues, and general use as a source of advice. A study by Elliott et al 11 indicated "self-selection" as one of two identification methods, although this method was described as identifying individuals who "expressed willingness to participate in the study. "…”
Section: Identification Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…25 This study queried respondents to rate themselves on a 1 to 5 scale (with 1 being low and 5 being high) for 6 items, including talking to colleagues, amount of information given during conversations, frequency of requests for information, relative likelihood of sharing with or receiving ideas from colleagues, and general use as a source of advice. A study by Elliott et al 11 indicated "self-selection" as one of two identification methods, although this method was described as identifying individuals who "expressed willingness to participate in the study. "…”
Section: Identification Methodsmentioning
confidence: 99%
“…Grimshaw, 25 as indicated previously, combined the sociometric and self-designating approaches to study general practitioner and specialist opinion leaders in Scotland. Elliott et al 11 used both sociometric (adapted Hiss et al 4 ) and self-selection (willingness to participate) approaches in their study of cancer pain management. A third study combined sociometric and informant methods to study strategies for improving breast-feeding rates.…”
Section: Identification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Classroom style teaching to healthcare professionals can improve knowledge of cancer pain management but there is good evidence that this has no significant impact on patient outcomes [1,6,18]. Encouraging a change in healthcare professional behavior (activity) is needed.…”
Section: Behavioural Mechanismsmentioning
confidence: 99%